Flt3 ligand expands CD4+FoxP3+ regulatory T cells in human subjects. Issue 2 (5th December 2012) - Klein, Oliver; Ebert, Lisa M.; Zanker, Damien; Woods, Katherine; Tan, Bee Shin; Fucikova, Jitka; Behren, Andreas; Davis, Ian D.; Maraskovsky, Eugene; Chen, Weisan; Cebon, Jonathan
<x xml:space="preserve">Abstract</x> CD4+CD25+FoxP3+ naturally occurring regulatory T (Treg) cells play a crucial role in the maintenance of immune tolerance and in preventing autoimmune pathology. Interventions that expand Treg cells are highly desirable, as they may offer novel treatment options in a variety of autoimmune and transplantation settings. Paralleling previous preclinical studies, we demonstrate here that administration of the hematopoietic growth factor Flt3L to human subjects increases the frequency and absolute number of Treg cells, and reduces the ratio of CD8+ T cells to Treg cells in the peripheral blood. The increase in Treg cells was due to enhanced Treg‐cell proliferation rather than release of Treg cells from the thymus. Further studies revealed that Flt3L‐induced proliferation of Treg cells was an indirect effect that occurred via the interaction of Treg cells with the Flt3L‐expanded pool of CD1c+ myeloid dendritic cells. On the basis of these findings, Flt3L may represent a promising agent for promoting immune tolerance in a variety of clinical settings.